(untitled) (Manila, 1996)
The Rice Genetics Collection of past symposia and other selected literature contains nearly 4,400 pages of searchable information on rice genetics and cytogenetics published by the IRRI and its partners since 1964. In addition to the five genetics symposia held at 5-year intervals since 1985, the collection contains classic publications that kicked off significant reporting on these subjects in the early 1960s. This collection is a comprehensive and historical documentation on the subject of rice genetics, spanning 45 years of research and scholarly work. Published in 1995, Rice Genetics III contains 138 chapters from various contributors on topics dealing with rice genetic research, including varietal differentiation and evolution; genetics of morphological and physiological traits and disease resistance; cytogenetics; tissue and cell culture; molecular mapping of genes; map-based gene cloning; molecular genetics of cytoplasmic male sterility; transformation; gene isolation, characterization, and expression; genetic diversity in pathogen populations; and rice research priorities.
Keywords: Rice genetics,Nhân giống lúa